Genome-Wide Analysis of microRNAs Identifies the Lipid Metabolism Pathway to Be a Defining Factor in Adipose Tissue From Different Sheep - Liu, Tian-Yi; Feng, Hui; Yousuf, Salsabeel; Xie, Ling-Li; Miao, Xiang-Yang (Frontiers in Veterinary Science, 2022)
MicroRNAs are a class of important non-coding RNAs, which can participate in the regulation of biological processes. In recent years, miRNA has been widely studied not only in humans and mice, but also in animal husbandry. However, compared with other livestock and poultry breeds, the study of miRNA in subcutaneous adipose tissue of sheep is not comprehensive. Transcriptome analysis of miRNAs in subcutaneous adipose tissue of Duolang sheep, and Small Tail Han sheep was performed using RNA-Seq technology. Differentially expressed miRNAs were screened between different breeds. Target genes were predicted, and then the joint analysis of candidate genes were conducted based on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Finally, the RNA-Seq data were verified by real-time quantitative polymerase chain reaction (qRT-PCR). Herein, we identified 38 differentially expressed miRNAs (9 novel miRNAs and 29 known miRNAs). In addition, a total of 854 target genes were predicted by miRanda software. GO and KEGG pathway analysis demonstrated that regulation of lipolysis in adipocytes plays a key role in the deposition of subcutaneous adipose tissue in Duolang sheep and Small Tail Han sheep. The miRNAs might regulate fat deposits by regulating genes involved in regulation of lipolysis in adipocytes. Specifically, NC_ 040278.1_ 37602, oar-mir-493-3p, NC_ 040278.1_ 37521 and NC_ 040255.1_ 11627 might target PTGS2, AKT2, AKT3, and PIK3CA, respectively, and then play critical regulatory role. In conclusion, all the results provide a good idea for further revealing the mechanism of subcutaneous adipose tissue deposition and improving the meat production performance of sheep, and lay a foundation for promoting the development of animal husbandry.